Equity valuation of Nike, Inc. - Balsinhas, Gonçalo Nuno Ferreira (2022)
With a leading position in the sportswear industry and one of the most valuable and reputable brands worldwide, Nike, Inc. is the world’s largest designer and manufacturer of athletic footwear and apparel company. Nike has kept its dominant market share position and its operations thriving despite the recent unfavorable macroeconomic situation, which was brought on by a global pandemic and escalating inflationary pressures. However, the stock market downturn of 2022 has had an impact on Nike's share price, with the company's shares declining by more than 38% since November of 2021. Therefore, the goal of this dissertation is to determine Nike, Inc.’s target share price for the end of the firm’s fiscal year of 2023 (31/05/2023) and provide a detailed investment recommendation based on the intrinsic value of Nike. A thorough research of Nike's industry, projections for the forthcoming macroeconomic environment, as well as a profound company research, were the pillars sustaining this valuation. Based on the conciliation of the author’s assumptions with the best firm valuation practices, the target value per Nike share was set at $108.68, derived from a WACCbased DCF approach, meaning a 2.6% upside potential. In the end, the results obtained were discussed through a sensitivity analysis and compared to other analyst’s forecasts, which, considering the uncertainty regarding the current economic context, supported a hold recommendation.